Heat exchanger member, heat exchanger, air conditioner, and refrigerator
A carbon-containing hydrated metal oxide film with fine irregularities on heat exchanger fins addresses the issues of power consumption and ventilation resistance by enhancing hydrophilicity and thermal conductivity, improving heat exchange efficiency and reducing dew droplet bridging.
Patent Information
- Application Number
- JP2021042273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-16
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-03-16
AI Technical Summary
Existing hydrophilic coatings on heat exchanger fins, such as those using acrylic resin or ceramic materials, increase power consumption and ventilation resistance due to low thermal conductivity and ineffective dew droplet removal.
A carbon-containing hydrated metal oxide film with fine irregularities is applied to the heat exchanger fins, enhancing hydrophilicity and thermal conductivity, allowing dew droplets to slide off easily and preventing bridging.
The solution improves heat exchange efficiency and reduces power consumption by effectively managing dew condensation and maintaining hydrophilicity over time, while maintaining the thermal conductivity of the metal base.
Smart Images

Figure 0007602251000001 
Figure 0007602251000002 
Figure 0007602251000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat exchanger member having a metal surface imparted with properties other than those inherent to the metal, and to a device including the member. [Background technology]
[0002] When an air conditioner is in operation, condensation and frost form on the surfaces of heat exchange fins of the heat exchangers installed in the indoor and outdoor units. This condensation and frost on the surfaces of the heat exchange fins have adverse effects such as a decrease in air blowing efficiency, a decrease in heat exchange performance, and an associated increase in power consumption of the air conditioner itself. In recent years, in the field of air conditioning, techniques related to hydrophilization have been actively studied as a measure against the condensation and frost on the surfaces of the heat exchange fins. Such techniques are disclosed, for example, in Patent Document 1.
[0003] Patent Document 1 describes a method for suppressing an increase in ventilation resistance caused by condensation on the heat exchange fins of a heat exchanger by forming a hydrophilic resin coating made of an acrylic resin (polyacrylic acid, acrylamino, acrylamide, etc.), a cellulose resin, a polyvinyl alcohol resin, an amide resin, an amino resin, etc. on the surface of the heat exchange fins. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-322469 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the technology of Patent Document 1 uses organic resins such as acrylic resins (about 1 / 180 of the thermal conductivity of aluminum oxide) that have significantly lower thermal conductivity than aluminum, which is a common material for heat exchange fins in heat exchangers, and aluminum oxide that is naturally formed on the surface of aluminum, and ceramic materials such as silica particles (about 1 / 20 of the thermal conductivity of aluminum oxide) and zeolite (about 1 / 180 of the thermal conductivity of aluminum oxide), which are also used in hydrophilic coating films. Therefore, there was a problem that the composition of the hydrophilic coating film itself, which is supposed to be a measure to increase the power consumption of air conditioners, increases the power consumption of the air conditioners when the air conditioners are operated in an environment where condensation does not occur.
[0006] Furthermore, hydrophilic technology that only reduces the contact angle has the problem that water droplets caused by actual condensation remain attached to the surface and do not slide off, ultimately causing ventilation resistance.
[0007] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a highly efficient heat exchanger component, heat exchanger, air conditioner, and refrigerator by providing a coating having excellent hydrophilicity and thermal conductivity to the metal surface forming a heat exchanger or the heat exchange fins of a heat exchanger, giving properties that the metal itself does not have. [Means for solving the problem]
[0008] In order to solve the above problems, the heat exchanger component of the present invention is a heat exchanger component made of metal, which has a metal oxide film having irregularities on the surface of the metal and containing crystalline carbon, the average distance between the apexes of the protrusions is 20 nm or more and 120 nm or less, the average height of the apexes of adjacent protrusions is 10 nm or more and 250 nm or less, and at least a portion of the surface of the metal oxide film is a hydrated oxide. Effect of the Invention
[0009] According to the present invention, it is possible to provide a heat exchanger member with a function of improving the heat exchange efficiency of the heat exchanger. [Brief description of the drawings]
[0010] [Figure 1] 1 is a perspective view showing an indoor unit of an air conditioner using a heat exchanger member according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing a heat exchanger member according to a first embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing a cross section taken along the line aa in FIG. 2. [Figure 4] FIG. 2 is a SEM perspective view of the surface of the heat exchanger member according to the first embodiment of the present invention. [Diagram 5] FIG. 1 is a diagram showing an equipment for producing embodiment 1 of the present invention. [Figure 6] FIG. 2 is a diagram showing a time chart of the load electric field density for producing the first embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Embodiment 1] Hereinafter, an embodiment of the present invention will be described with reference to FIGS.
[0012] <Configuration of an indoor unit of an air conditioner incorporating the components> 1 is a diagram showing a cutaway model of an air conditioner indoor unit 100. The air conditioner indoor unit 100 is composed of a heat exchanger 110, an air filter 120, a blower fan 130, a drain pan 140, a housing 150, and a control unit, a drive unit, etc., which are not shown.
[0013] Heat exchanger 110 is composed of refrigerant pipes 111 and fins 112. The heat exchanger member of the present invention means a member constituting heat exchanger 110 (refrigerant pipes 111 and fins 112). In the following explanation, the heat exchanger member will be explained as a member constituting fins 112.
[0014] <Component composition> 2 and Fig. 3, which is a cross-sectional view taken along line aa of Fig. 2, are diagrams showing fins 112 constituting a heat exchanger 110, which is a specific example of a heat exchanger member of the present invention. As shown in Fig. 3, a carbon-containing hydrated oxide film 112B having fine irregularities 112C is provided on a metal base material 112A made of a main material (aluminum, copper, etc.) that forms the fin 112. The carbon-containing hydrated oxide film 112B having the fine irregularities 112C is a hydrated metal oxide film that contains carbon and is at least partially hydrated, and provides the function of improving the heat exchange efficiency of the heat exchanger 110.
[0015] Fins 112 are made of rolled aluminum plates or rolled copper plates. The thickness of fins 112 may be 0.05 to 0.50 mm. Furthermore, the thickness of fins 112 is preferably 0.05 to 0.20 mm so that a heat exchanger of the same volume can have a larger surface area than fins 112 when configured as a heat exchanger. The size is determined appropriately depending on the purpose of use.
[0016] The carbon-containing hydrated oxide film 112B is an oxide of the same or similar metal as the metal base material containing carbon, and at least a part of it is a hydrated metal oxide. The thickness of the carbon-containing hydrated oxide film 112B may be 40 nm to 300 nm. Furthermore, the thickness of the carbon-containing hydrated oxide film 112B is preferably 100 nm to 300 nm in order to utilize the thermal conductivity of the carbon contained therein and improve corrosion resistance. The carbon content of the carbon-containing hydrated oxide film 112B may be 1 at % to 50 at % at a point 3 nm to 5 nm from the surface (the surface opposite to the surface in contact with the metal base 112A). Furthermore, the carbon content of the carbon-containing hydrated oxide film 112B is preferably 3 at % to 40 at % at a point 3 nm to 5 nm from the surface in order to provide the properties imparted by the inclusion of carbon and to maintain the strength of the film.
[0017] The carbon contained in the carbon-containing hydrated oxide film 112B is preferably crystalline, and carbon nanotubes, fullerenes, graphene, and the like are preferred in order to enhance thermal conductivity.
[0018] Although carbon nanotubes, fullerenes, graphene, etc. are expensive, the carbon-containing hydrated oxide film 112B containing these is extremely thin compared to so-called coatings, and the amount actually contained is very small, making it advantageous in terms of cost.
[0019] The fine irregularities 112C are provided on the surface of the carbon-containing hydrated oxide film 112B (the surface opposite to the surface in contact with the metal base 112A), and it is sufficient that the average interval between the apexes of the protrusions of the fine irregularities 112C is 20 nm or more and 120 nm or less, and the average value of the difference in height between the apexes of the protrusions and the bottom points of the recesses adjacent to each other is 10 nm or more and 250 nm or less. Furthermore, in order to impart more hydrophilicity to the fine irregularities 112C, it is more preferable that the average value of the difference in height between the apexes of the protrusions and the bottom points of the recesses is 100 nm or more and 200 nm or less.
[0020] An example according to the first embodiment will be described below with reference to Fig. 5 and Fig. 6. The fin 112 in the example is made of an aluminum plate measuring 60 mm x 60 mm x 0.5 mm. The following treatment was carried out to provide a carbon-containing hydrated oxide film 112B having fine irregularities 112C on the surface of this aluminum plate (metal base 112A).
[0021] First, this aluminum plate (metal base 112A) is ultrasonically cleaned (cleaning time: 5 minutes) with ethanol of 99.5% purity. Then, the aluminum plate connected to an electric circuit 400 and SUS304 electrodes 404, 405 connected to the electric circuit 400 are immersed in a bath 300 containing a processing liquid 301, as shown in Fig. 5. The processing liquid 301 in the bath 300 is made by adding sodium hydroxide and a 0.2% carbon nanotube dispersion liquid to purified water so that the concentrations are 1.7 g / l and 1.64 ml / l, respectively, and the liquid temperature is room temperature (20 to 30°C).
[0022] Thereafter, assuming that the current flowing in the direction of the arrow shown in FIG. 5 is a positive voltage, a voltage was applied to the aluminum plate by rectifiers 401 and 402 and changeover switch 403 in the pattern shown in FIG. 6.
[0023] Next, the aluminum plate is ultrasonically cleaned with purified water (cleaning time: 5 minutes). The aluminum oxide on the surface of the aluminum plate is hydrated by immersing it in hot water at 98°C for 15 minutes, and finally dried by air blowing. In this way, a carbon-containing hydrated oxide film 112B of 200 nm is provided on the surface of the aluminum plate (metal base 112A), and at the same time, fine irregularities 112C are provided on the surface of the carbon-containing hydrated oxide film 112B, in which the average interval between the apexes of the uneven shape of the protrusions is 75 nm and the average difference in height between the apexes of the adjacent protrusions and the bottom points of the recesses is 50 nm, to form fins 112.
[0024] <Demonstration test> Here, the characteristics required for the fins constituting the heat exchanger will be explained. In a heat exchanger, a large number of fins for heat exchange are arranged with very narrow gaps. Therefore, when used to take heat from the outside air, condensation occurs on the fin surface. In an indoor unit during cooling operation, condensation creates a bridge of water droplets between the fins, hindering ventilation between the fins. As a result, condensation inhibits the heat conversion efficiency of heat exchange. In this way, by preventing the bridge of water droplets between the fins due to condensation, the heat exchange efficiency of the heat exchanger can be significantly improved. However, it is difficult to prevent the occurrence of condensation itself, and the only way to suppress the bridge of condensation water is to apply a hydrophilic coating to the fins to perform a hydrophilic treatment, but the contact angle is not sufficiently low and the water droplets themselves do not slide off, so the water droplets accumulate and eventually form bridges, and it was not possible to sufficiently suppress it.
[0025] Furthermore, the contact angle reduction effect of the hydrophilic coating was not durable, and the contact angle quickly increased when condensation and drying were repeated, so it lacked long-term suppression effect.
[0026] Furthermore, the above-mentioned hydrophilic treatment involves the application of acrylic resin, silica particles, zeolite, etc., which have lower thermal conductivity than the aluminum oxide that naturally forms on the surface of aluminum, resulting in a problem of a decrease in the essential heat exchange rate.
[0027] The fins 112 constituting the heat exchanger of the present invention, although the mechanism is unclear, have a remarkable effect of suppressing bridging of condensation water by reducing the contact angle and allowing attached water droplets to slide off easily. Also, because the carbon-containing hydrated oxide film 112B containing carbon with higher thermal conductivity than aluminum oxide on the surface of the aluminum is provided, the heat exchange efficiency of aluminum, which is the main material of the fins 112, is not hindered compared to general hydrophilic treatments that provide acrylic resins, silica particles, zeolite, etc., which have lower thermal conductivity than aluminum.
[0028] The contact angle and sliding angle with water were measured for each of the fin 112 constituting the heat exchanger of the present invention shown in Fig. 4, the comparative fin 113 made of an untreated aluminum plate equivalent to the aluminum plate before the treatment for forming the carbon-containing hydrated oxide film described above for comparison (not shown), the comparative fin 114 made of an untreated aluminum plate (not shown) that has only been subjected to a hydration treatment, and the comparative fin 115 made of an untreated aluminum plate (not shown) that has been coated on its surface with a silica-based hydrophilic coating used in current air conditioners. As a result, the fin 112 of the present invention had a contact angle of 17° and a sliding angle of 26°, the comparative fin 113 had a contact angle of 93° and did not slide, the comparative fin 114 had a contact angle of 46° and did not slide, and the comparative fin 115 had a contact angle of 14° and did not slide.
[0029] The sliding angle mentioned above is the angle at which a droplet of 10 μl of purified water begins to slide when the plate to be measured is tilted at a specified speed after being dropped onto the plate, which is placed horizontally. In other words, a smaller sliding angle means that the condensed droplet slides off more easily, and that compared to a simple smaller contact angle, a bridge of droplets between the fins is less likely to form.
[0030] From the above results, it was confirmed that the fin 112 of the present invention has a higher water droplet bridge suppressing effect than the comparative fins 113 to 115.
[0031] In addition, the heat exchange fins used in air conditioners are used for long periods of time while repeatedly undergoing the adhesion of water droplets due to condensation and drying during periods of inactivity, so it is important to maintain not only the initial characteristics but also the characteristics after repeated adhesion and drying of water droplets.
[0032] Therefore, a wet-dry test is used as an accelerated test of the cycle of water droplet adhesion and drying. When the above-mentioned dry test was performed on the fin 112 of the present invention and the comparative fin 115, the increase in the contact angle after the test was 5° and 55°, respectively. From the above results, it was confirmed that the fin 112 of the present invention has excellent property retention.
[0033] Furthermore, a heat exchanger (not shown) was fabricated using the fins 112 of the present invention and the comparative fins 113, and placed in an airtight box allowing air to circulate inside. The cooling characteristics were confirmed under low humidity conditions (26°C, 30% RH). In the heat exchanger using the fins 112 of the present invention, the temperature reached after two hours was 5.6°C, but in the heat exchanger using the comparative fins 113, the temperature could only be cooled to 7.6°C. In other words, although the exact reason is unclear at this point, it can be said that the fins of the present invention have excellent heat exchange properties regardless of condensation.
[0034] In this embodiment, the wet electrolytic treatment under the above conditions was used to form the carbon-containing hydrated oxide film 112B having the fine irregularities 112C on its surface, but the present invention is not limited to this and the film may be formed under other conditions or by other treatment methods (such as sputtering or a sol-gel method using a metal oxide target containing carbon nanotubes) and then hydrated. However, the wet electrolytic treatment is more cost-effective than other treatment methods.
[0035] In this way, the fins 112 of the present invention have the advantage of suppressing the reduction in ventilation caused by condensation water bridges, compared to conventional hydrophilic treatments using hydrophilic coatings, and of improving the heat exchange rate of the heat exchanger even when condensation does not occur.
[0036] Moreover, the first embodiment of the present invention is not limited to the fins 112, but may be, for example, a copper cooling water pipe for a radiator or a member constituting a water-cooling jacket for cooling a power device, and in either case, the same effect as that of the fins 112 is obtained. In addition, the carbon-containing hydrated oxide film 112B also has the effect of improving the corrosion resistance of the member.
[0037] Moreover, a heat exchanger constituted by members such as the fins 112 achieves the same effects as the fins 112.
[0038] Furthermore, it is clear that an air conditioner or a refrigerator provided with a heat exchanger constituted by members such as the fins 112 also provides the same effect as the fins 112, and therefore, as a result, it provides the effect of reducing power consumption.
[0039] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in the different embodiments. Furthermore, new technical features can be formed by combining the technical means disclosed in the respective embodiments. [Industrial Applicability]
[0040] INDUSTRIAL APPLICABILITY The present invention can be used in heat exchanger components in which it is necessary to suppress a decrease in ventilation caused by condensation water bridges. [Explanation of symbols]
[0041] 100…Indoor unit of air conditioner 112…Fin 112B…Carbon-containing hydrated metal oxide film (metal oxide film) 112C...Minute unevenness 300…Treatment tank 400…Electrical circuit
Claims
1. A heat exchanger member made of a metal, A metal oxide film containing crystalline carbon is provided on the surface of the metal, The surface is uneven only by the metal oxide film, the average interval between the apexes of the protrusions is 20 nm or more and 120 nm or less, and the average height of the apexes of adjacent protrusions is 10 nm or more and 250 nm or less, A heat exchanger member, characterized in that the surface of the metal oxide film is a hydrated oxide, and the surface exhibits hydrophilicity.
2. A heat exchanger member made of a metal, The metal has a metal oxide film having an uneven surface and containing crystalline carbon, the average interval between the apexes of the protrusions is 20 nm or more and 120 nm or less, and the average height of the apexes of adjacent protrusions is 10 nm or more and 250 nm or less, and the surface of the metal oxide film is a hydrated oxide and is hydrophilic; A heat exchanger member, characterized in that the content of crystalline carbon contained in the metal oxide film within a range of 3 to 5 nm from the surface is 3 at % or more and 40 at % or less.
3. 3. The heat exchanger member according to claim 1, wherein the metal oxide film has a thickness of 100 nm or more and 300 nm or less.
4. A heat exchanger comprising a heat exchange fin made of the heat exchanger member according to any one of claims 1 to 3.
5. 5. An indoor unit for an air conditioner, comprising the heat exchanger according to claim 4.
6. 5. An outdoor unit for an air conditioner, comprising the heat exchanger according to claim 4.
7. A refrigerator comprising the heat exchanger according to claim 4.
Citation Information
Patent Citations
Aluminum fin material for heat exchanger of air conditioner, whose surface is treated with hydrophilic coating
JP1993322469A
Air conditioner, heat exchanger and its production
JP1998281690A
Refrigerator, and manufacturing method for evaporator for refrigerator chamber for use in former
JP2001248951A
Heat exchanger and deodorizing and sterilizing device
JP2005207612A
Heat exchanger
JP2016061526A
